Influence of parents' jobs on apprentices' work values - Abdullah, Nur Surayyah Madhubala; Chee, Chen Soon; Md. Aroff, Abdul Rahman (Universiti Putra Malaysia Press, 2014)
This paper presents the findings of a study into the relationship between parents' jobs and the work values of apprentices. The findings were examined in the context of the positive relationship between work commitment and productivity of skilled workers and the need to understand influences on the work values of apprentices. The findings showed that the work values of apprentices were influenced by the kind of jobs each parent held. The importance of particular work values to apprentices differed significantly according to either their mother or father's job. ANOVA and Post Hoc analyses showed that the parents' role in their children's work values depended on the work value examined. The findings support literature specifically on intergenerational transmission of values, the occupational linkage hypothesis and the social learning theory on the influence of parents' occupation and children's values. They also show the importance for industry to focus on, and provide support to young apprentices in improving their commitment to work and help raise their productivity levels. The paper offers some suggestions on the kind of focus and support that can be offered.